A comparison of avian habitat in forest management plans produced under three different certification systems in Ontario, Canada. (9th January 2014) - Euler, David
ABSTRACT Considerable discussion and theoretical reviews of forest certification systems have been published that outline the potential impact of forest certification on biodiversity and wildlife habitat. Three common approaches to forest certification used in Canada include the Forest Stewardship Council, the Canadian Standards Association, and the Sustainable Forestry Initiative. In this study, I reviewed forest management plans in Ontario, Canada, and compared the plans' potential impact on habitat for 6 species of birds that use mature and older forests: pileated woodpecker (Dryocopus pileatus), ruby‐crowned kinglet (Regulus calendula), boreal chickadee (Poecile hudsonicus), black‐backed woodpecker (Picoides arcticus), great gray owl (Strix nebulosa), and red‐breasted nuthatch (Sitta canadensis). The purpose was to determine whether the different certification systems in use resulted in different impacts on avian habitat, and to compare certified forest management plans with plans prepared for un‐certified forest units. Based on 27 Forest Management Plans in Ontario, there seems to be little reason to believe that certified forests are more likely to protect and conserve habitat for these 6 bird species that use older forests than are forests that are not certified. © 2014 The Wildlife Society.